2007
DOI: 10.1158/0008-5472.can-06-3697
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and Nontargeted Effects of Low-Dose Ionizing Radiation on Delayed Genomic Instability in Human Cells

Abstract: All humans receive some radiation exposure and the risk for radiation-induced cancer at low doses is based on the assumption that there is a linear non-threshold relationship between dose and subsequent effect. Consequently, risk is extrapolated linearly from high radiation doses to very low doses. However, adaptive responses, bystander effects, and death-inducing effect may influence health effects associated with low-dose radiation exposure. Adaptive response is the phenomenon by which cells irradiated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 46 publications
2
50
0
1
Order By: Relevance
“…Some of them are clastogenic and can induce chromosomal damage in nonirradiated cells, analogous to that in directly-hit cells. Huang et al (2007) observed that growth medium conditioned by some chromosomally unstable RKO derivatives induced genomic instability, indicating that these cells can secrete factor(s) that elicit responses in non-irradiated cells. Furthermore, low radiation doses suppressing the induction of delayed genomic instability by a subsequent high dose, are indicative of an adaptive response for radiation-induced genomic instability.…”
Section: Radiation Induced Bystander Effect Genetic Instability and mentioning
confidence: 99%
“…Some of them are clastogenic and can induce chromosomal damage in nonirradiated cells, analogous to that in directly-hit cells. Huang et al (2007) observed that growth medium conditioned by some chromosomally unstable RKO derivatives induced genomic instability, indicating that these cells can secrete factor(s) that elicit responses in non-irradiated cells. Furthermore, low radiation doses suppressing the induction of delayed genomic instability by a subsequent high dose, are indicative of an adaptive response for radiation-induced genomic instability.…”
Section: Radiation Induced Bystander Effect Genetic Instability and mentioning
confidence: 99%
“…Morgan (2006) has recently suggested that the issue of the validity of the Linear-No Threshold hypothesis hinges on the significance of the adaptive response protection versus the deleterious bystander damage with little significance placed on apoptosis and genomic instability. Even more recent work (Huang et al 2007) finds that genomic instability experiences an adaptive response suppression from low-dose radiation exposure.…”
Section: Known Protective and Deleterious Low Level Mechanisms And Thmentioning
confidence: 99%
“…These biological effects are attributed to unrepaired or misrepaired DNA damage in cells directly hit by radiation. However, the effects of ionizing radiation also extend to cells that were not themselves irradiated, but were neighbors or the progeny of irradiated cells [Huang et al, 2007;Sowa, 2007, 2009;Kovalchuk and Baulch, 2008;Rzeszowska-Wolny et al, 2009;Wright, 2010]. The molecular mechanisms of these non-targeted effects are a matter of intensive investigation and are not fully understood.…”
Section: Introductionmentioning
confidence: 99%